Photocatalytic CO2 reduction and environmental remediation using mineralization of toxic metal cations products - Lai, T; Wang, J; Xiong, W; Wang, H; Yang, M; Li, T; Kong, X; Zou, X; Zhao, Y; O'Hare, D; Song, Y-F (Elsevier, 2022)
Exploring a sustainable route for the efficient treating/recycling of heavy metal (like Ni2+, Cd2+, Cu2+) contamination of water is highly desirable both from the environment and resource view. Herein, we reported the scale-up synthesis of monolayer magnesium-aluminium layered double hydroxide (m-MgAl-LDH) nanosheets, which showed exceptional ability to mineralize Ni2+, Cd2+ and Cu2+ rapidly and efficiently. Furthermore, m-MgAl-LDH can purify 1 ppm Cu2+, Ni2+ and Cd2+ to safe levels. The sorption sites of heavy metal ions were revealed. Ni2+ and Cd2+ substitute for the Mg2+ sites within the MgAl-LDH layers, while Cu2+ ions anchor on the surface of MgAl-LDH with high dispersion. The mineralized products from Ni2+ and Cu2+ cations further showed excellent performance in visible-light-induced photocatalytic reduction of CO2 and removal of anions (like PO43- and toxic AsO2- ions) efficiently, providing an alternative for the mitigation of energy and resource crisis.